Reciprocal lending relationships in shadow banking - Li, Yi (Journal of Financial Economics, 2021)
Postcrisis regulations apply stricter liquidity rules to both money market funds (MMFs) and banks, requiring MMFs to do more overnight lending and banks to borrow longer-term. MMFs and banks resolve this dilemma by developing a “bundling” strategy across overnight and longer term markets. In particular, MMFs increase longer term funding and charge a lower rate to banks that have recently accommodated MMFs’ overnight depositing needs. Such cross-market reciprocity is stronger between MMFs and foreign banks, which depend on MMFs for dollar funding more than U.S. banks do. MMFs with lower liquidity buffers and higher flow volatility are more likely to engage in bundling.